Water content of pomegranate seeds subjected to storage and packaging periods - Monteiro, Laís Naiara Honorato; Ferreira, Antonio Flavio Arruda; Rodrigues, Maria Gabriela Fontanetti; Faria, Glaucia Amorim; Boliani, Aparecida Conceição (Comunicata Scientiae, 2021)
The worldwide demand for unconventional fruits, such as pomegranate (Punica granatum L.), has been growing due to their nutraceutical characteristics. Given the social and industrial importance of the crop, information about the seed storage conditions should be elucidated to technify its cultivation. The objective of this work was to evaluate, by determining the water content, the behavior of pomegranate seeds when stored in different periods and packages. The seeds were separated into 2 lots: seeds with sarcotesta and for another lot, seeds without sarcotesta. The storage periods used were: 0, 30, 60, 90 and 120 days, in 3 types of packaging (polyethylene, paper bags and glass bottles), which were stored in BOD at 5±0.2ºC and relative humidity 35±2%. After storage periods, the seed water content was evaluated. Throughout storage periods, polyethylene containers reduced the water content of seeds with and without sarcotesta. Paper bags did not preserve the water content of both types of pomegranate seeds. The water content of pomegranate seeds with and without sarcotesta was better conserved when glass containers were used for storage.